Usp14 down-regulation corrects sleep and circadian dysfunction of a Drosophila model of Parkinson’s disease - Favaro, Mariavittoria; Mauri, Sofia; Bernardo, Greta; Zordan, Mauro A.; Mazzotta, Gabriella M.; Ziviani, Elena (Frontiers in Neuroscience, 2024)
PD is a complex, multifactorial neurodegenerative disease, which occurs sporadically in aged population, with some genetically linked cases. Patients develop a very obvious locomotor phenotype, with symptoms such as bradykinesia, resting tremor, muscular rigidity, and postural instability. At the cellular level, PD pathology is characterized by the presence of intracytoplasmic neurotoxic aggregates of misfolded proteins and dysfunctional organelles, resulting from failure in mechanisms of proteostasis. Nonmotor symptoms, such as constipation and olfactory deficits, are also very common in PD. They include alteration in the circadian clock, and defects in the sleep-wake cycle, which is controlled by the clock. These non-motor symptoms precede the onset of the motor symptoms by many years, offering a window of therapeutic intervention that could delay - or even prevent - the progression of the disease. The mechanistic link between aberrant circadian rhythms and neurodegeneration in PD is not fully understood, although proposed underlying mechanisms include alterations in protein homeostasis (proteostasis), which can impact protein levels of core components of the clock. Loss of proteostasis depends on the progressive pathological decline in the proteolytic activity of two major degradative systems, the ubiquitin-proteasome and the lysosome-autophagy systems, which is exacerbated in age-dependent neurodegenerative conditions like PD. Accordingly, it is known that promoting proteasome or autophagy activity increases lifespan, and rescues the pathological phenotype of animal models of neurodegeneration, presumably by enhancing the degradation of misfolded proteins and dysfunctional organelles, which are known to accumulate in these models, and to induce intracellular damage. We can enhance proteostasis by pharmacologically inhibiting or down-regulating Usp14, a proteasome-associated deubiquitinating enzyme (DUB). In a previous work, we showed that inhibition of Usp14 enhances the activity of the ubiquitin-proteasome system (UPS), autophagy and mitophagy, and abolishes motor symptoms of two well-established fly models of PD that accumulate dysfunctional mitochondria. In this work we extended the evidence on the protective effect of Usp14 down-regulation, and investigated the beneficial effect of down-regulating Usp14 in a Pink1 Drosophila model of PD that develop circadian and sleep dysfunction. We show that down-regulation of Usp14 ameliorates sleep disturbances and circadian defects that are associated to Pink1 KO flies.